Environmental Contaminants in Colonial Waterbirds from Great Slave Lake, NWT: Spatial, Temporal and Food-chain Considerations - Wayland, Mark; Hobson, Keith A.; Sirois, Jacques (ARCTIC, 2000)
Great Slave Lake in the Northwest Territories, Canada, differs regionally in trophic status and local and regional inputs of contaminants. Spatial and temporal trends in contaminant levels in bioindicator species such as colonial waterbirds could offer insights into the potential for contaminant bioaccumulation in Great Slave Lake. Persistent chlorinated hydrocarbon contaminants, mercury (Hg), and selenium (Se) were examined in herring gull (Larus argentatus) eggs and livers collected from various locations on Great Slave Lake in 1995. Eggs were collected in May and June, and livers in May and August. Also, the relationship between contaminants and trophic level, as inferred from stable-nitrogen isotope analysis (delta 15N), was examined in four colonial waterbird species: herring gull, mew gull (L. canus), Caspian tern (Sterna caspia), and black tern (Chlidonias niger). Finally, the co-accumulation of mercury and selenium was examined in eggs of these birds. There were no differences in chlorinated hydrocarbon concentrations among four sampling sites (colonies). Concentrations did not differ between herring gull adults collected in early May and those collected in early August. Chlorinated hydrocarbon concentrations in eggs of herring gull, mew gull, Caspian tern, and black tern were related to their trophic positions as inferred from their delta 15N values in their lipid-free egg yolks. Concentrations in these colonial waterbirds were much higher than those in fish from Great Slave Lake, but lower than those in their conspecifics from the Great Lakes. It is probable that a relatively large proportion of the chlorinated hydrocarbon contaminant load in colonial waterbird eggs on Great Slave Lake results from exposure to and storage of such contaminants at more heavily contaminated wintering and staging areas. This possibility limits the usefulness of colonial waterbirds as indicators of chlorinated hydrocarbon bioaccumulation in Great Slave Lake. Selenium and mercury concentrations in herring gull eggs differed ...